Capacidade discriminativa dos instrumentos do risco de sarcopenia sarc-f e sarc-calf na identificação de comprometimento funcional em pessoas idosas comunitárias - Fernandes, Marcia de Araújo Corcino (2024)
INTRODUCTION: Aging leads to a series of physiological changes and adaptations. There is a progressive and generalized reduction in muscle mass and strength. Sarcopenia is defined not only by the progressive and generalized decline in skeletal muscle mass but also by the reduction in muscle strength and physical performance, and it is associated with unfavorable outcomes. Tests and tools are used to assess its severity and impact on muscle performance. OBJECTIVE: To identify the risk of sarcopenia and assess the discriminative capacity of positive sarcopenia screening by the SARC-F and SARC-CalF instruments in determining reduced functional performance in elderly residents of a small municipality. METHODOLOGY: This is a cross-sectional observational study of a descriptive and quantitative nature and an analysis of discriminatory capacity. The data analyzed refer to the first wave of the EPI_força Jacaraú study, collected between December 2023 and May 2024. The project was approved by the Research Ethics Committee: CAAE: 74096623.7.0000.5188. A semi-structured instrument was used. Statistical analysis was performed using R® software (version 4.1.3). Descriptive statistics used absolute frequency tables (n) and relative frequency (%). The association between each functional performance exposure and the risk of sarcopenia was determined using the Chi-Square test. Discriminatory capacity was determined by the Area Under the Curve (AUC) generated by the ROC Curve. RESULTS: The prevalence of risk for sarcopenia identified by SARC-F was 20.2%, and by SARC-CalF, it was 27.3%. The sample was predominantly female, with an average age of 71.61 years, self-identified as Black or Brown, living in urban areas, married or in a stable union, living with 1 or 2 people, with an average of 4 years of education, and with a per capita household income of less than one minimum wage. The profile followed the trend of samples in elderly populations. The risk of sarcopenia identified by SARC-F showed a univariate association with all the tests assessed, and those at risk had a higher likelihood of having low grip strength, slow gait speed, low lower limb strength, and absence of balance in the feet-together, semi-tandem, and tandem postures. In contrast, SARC-CalF was associated with grip strength, gait speed, and tandem balance and had a higher likelihood of low grip strength, slow gait speed, low lower limb strength, and absence of balance in the tandem posture. The discriminative capacity of SARC-F is higher in the evaluated balance postures. The discriminative capacities of SARC-F and SARC-CalF were similar for gait speed and lower limb strength. For grip strength, the discriminative capacity of SARC-CalF was higher. CONCLUSION: The AUC values obtained by both instruments ranged from 0.51 to 0.8, indicating good discriminatory capacity for all the tests assessed.